Implementasi Layanan Konseling Profesional Menyeluruh dalam Lima Wilayah Kegiatan untuk Mewujudkan Perilaku Positif Terstruktur - Famahato Lase (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2021)
The purpose of this study is to describe the results of the implementation of comprehensive professional counseling in five areas of activity to realize structured positive behavior. The research approach used is the case study method. The source of data as well as the research subject is one client and the instrument for collecting data is the researcher himself as well as a counselor. From the results of the research that has been carried out, it is revealed that concretely the successful realization of structured positive behavior along with elements of reference, competence, effort, taste, sincerity, related to the development of effective daily life and alleviation of problems experienced to completion is the result of counseling. The results, are: 1) The negative reference, effective daily living conditions and problems experienced as well as negative conditions of thinking, feeling, acting, acting, and being responsible clients are changed to positive ones, namely the intention to commit suicide and/or abortion is canceled or modified; 2) Competence, the client has the ability to think, feel, behave, act, and be responsible in a positive way, and will be successful in positive structured behavior with effective daily life developing and overcoming problems experienced; 3) Effort, the client is actually trying to do structured positive behavior; 4) Taste, the client feels he has to get out of the problem immediately; 5) Sincerity, the client tries seriously to act and do what he has thought, felt, taken a positive attitude, acted and took full responsibility to the end.